2019
DOI: 10.3390/jcm8081164
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Belatacept Treatment in Renal Allograft Recipients at High Cardiovascular Risk—A Single Center Experience

Abstract: Belatacept is an attractive option for immunosuppression after renal transplantation. Renal allograft function is superior when compared to calcineurin inhibitor (CNI) based therapy in “de novo” treated patients and it has also been proposed that individuals at high cardiovascular (CV) risk may benefit most. In this retrospective cohort study, we assessed the efficacy and safety of treating patients at high cardiovascular risk with Belatacept (n = 34, for 1194 observation months) when compared to a matched con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Currently, calcineurin inhibitors (CNIs) are the standard immunosuppressive therapy after renal transplantation ( 31 ). Previous studies have observed that CNIs, including tacrolimus and cyclosporin A (CsA), are risk factors for HUA after renal transplantation ( 1 , 22 , 32 ).…”
Section: Risk Factors For Hua After Renal Transplantationmentioning
confidence: 99%
“…Currently, calcineurin inhibitors (CNIs) are the standard immunosuppressive therapy after renal transplantation ( 31 ). Previous studies have observed that CNIs, including tacrolimus and cyclosporin A (CsA), are risk factors for HUA after renal transplantation ( 1 , 22 , 32 ).…”
Section: Risk Factors For Hua After Renal Transplantationmentioning
confidence: 99%